Brucella abortus RNA does not polarize macrophages to a particular profile but interferes with M1 polarization - Serafino, Agustina (2022)
Monocytes and macrophages play a central role in chronic brucellosis. Brucella abortus (Ba) is an intracellular pathogen that survives inside these cells. On the other hand, macro-phages could be differentiated into classical (M1), alternative (M2) or other less-identified profiles. We have previously shown that Ba RNA (a bacterial viability-associated PAMP or vita-PAMP) is a key molecule by which Ba can evade the host immune response. However, we did not know if macrophages could be polarized by this vita-PAMP. To assess this, we used two different approaches: we evaluated if Ba RNA per se was able to differentiate mac-rophages to M1 or M2 or, given that Ba survives inside macrophages once a Th1 response is established (i.e., in the presence of IFN-γ), we also analysed if Ba RNA could interfere with M1 polarization. We found that Ba RNA alone does not polarize to M1 or M2 but activates human macrophages instead. However, our results show that Ba RNA does interfere with M1 polarization while they are being differentiated. This vita-PAMP diminished the M1-induced CD64, and MHC-II surface expression on macrophages at 48 h. This phenomenon was not associated with an alternative activation of these cells (M2), as shown by unchanged CD206, DC-SIGN and CD163 surface expression. When evaluating glucose metabolism, we found that Ba RNA did not modify M1 glucose consumption or lactate pro-duction. However, production of Nitrogen Reactive Species (NRS) did diminish in Ba RNA-treated M1 macrophages. Overall, our results show that Ba RNA could alter the proper immune response set to counterattack the bacteria that could persist in the host establishing a chronic infection.